ISLAMIC RELIGIOUS EDUCATION TEACHER STRATEGIES IN FOSTERING MULTICULTURAL EDUCATION AT PUBLIC JUNIOR HIGH SCHOOL 7 MATARAM - Fitrah Jaiman; Ismail Thoib; Emawati Emawati (Conciencia, 2022)
There is a lot of diversity in religion, culture, language, ethnicity, and customs in SMP Negeri 7 Mataram school. But this is not a trigger for the birth of conflict. This research was conducted at SMP Negeri 7 Mataram. This research aims to analyze the strategy of Islamic Religious Education Teachers in fostering students' multicultural education. The approach used is qualitative with the case study method. Data collection techniques are done by interview, observation, and documentation. The data analysis process uses Miles and Huberman's theory: data reduction, display, and verification. The results of the study state that the strategy of Islamic Religious Education teachers in fostering students' multicultural education is done through promoting and strengthening attitudes, providing freedom, teaching knowledge or integration, providing equal treatment, and counseling multicultural reinforcement.